Organizing Labs for Administrating Operating Systems Using Hyper-V - Oleksiy Naumuk (Pedagogical Discourse, 2013)
The article analyzes the role of the modern computer science teachers and how to improve its training courses in the study of the «Administration of Computer Networks» and «Computer Network». It highlights potential complications and problems in the preparation of equipment for practical training in these disciplines. It explains how to install and configure some features of Microsoft Hyper-V versions Server Core and Full Installation, using console Hyper-V Manager to manage virtualization. The review of virtualization technology to organize workshops is carried out. Based on the opportunities provided by the hypervisor it can be concluded that the implementation of virtualization on a practical training will enhance practical skills, improved absorption of the theoretical material on administration of operating systems and computer networks.